2016
DOI: 10.15226/jnhfs.2016.00171
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Diet Quality Score for Infants and Toddlers and its Association with Weight

Abstract: Objective To create a Diet Quality Index Score (DQIS) for infants and toddlers and to assess its relative validity. Design Three DQIS were created (0–5, 8–11 and 12–24 months) based on a validated food frequency questionnaire (FFQ). Nine components were included, scored from 0 (inadequate) to 5 (adequate consumption) based on guidelines for timing of food’s introduction and portion sizes; the component on breastfeeding (Yes/No) was scored (0–15). Infants 6–7 months were excluded as new foods are introduced d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…Despite considerable interest in the diet quality of children, particularly those below 2 years of age [9], diet quality indices are relatively less developed in pediatric populations compared to adult populations [8]. Dietary intakes in the first two years of life are varied and less stable as toddlers are introduced to many new food and beverages during this period [10]. It may be difficult to quantify toddlers’ portion sizes as food wastage and fussy eating are prevalent among this age group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite considerable interest in the diet quality of children, particularly those below 2 years of age [9], diet quality indices are relatively less developed in pediatric populations compared to adult populations [8]. Dietary intakes in the first two years of life are varied and less stable as toddlers are introduced to many new food and beverages during this period [10]. It may be difficult to quantify toddlers’ portion sizes as food wastage and fussy eating are prevalent among this age group.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, food-based dietary guidelines with quantifiable recommendations for children below 2 years old are limited internationally [11]. Existing studies in Western countries (e.g., Netherlands [12], Puerto Rico [10] and Australia [13,14]) where diet quality indices for children have been developed and validated have demonstrated that lower index scores were generally associated with unhealthy maternal lifestyle factors such as smoking during pregnancy [12], tended to associate with higher risk of excessive weight status in toddlers [10], shorter breastfeeding duration and greater food neophobia behavior [13]. However, to our knowledge, no diet quality index has been developed for Asian toddlers in a developed country.…”
Section: Introductionmentioning
confidence: 99%
“…The studies included in the qualitative synthesis were published between 2000 and 2020, with the majority (n 26) after 2010 (26,27,29,(31)(32)(33)(34)(35)(36)(37)(38)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(52)(53)(54)56) . Six studies were published between 2019 and 2020 (27,37,42,45,50,53) .…”
Section: Overview Of the Studiesmentioning
confidence: 99%
“…Twenty-four studies employed a cross-sectional design (10,(25)(26)(27)(28)(29)31,32,34,37,38,40,43,44,48,49,(52)(53)(54)(56)(57)(58)(59) , six were longitudinal studies (36,39,42,(45)(46)(47) , five were intervention studies (30,33,35,41,50) and one presented cross-sectional and longitudinal analyses (55) .…”
Section: Overview Of the Studiesmentioning
confidence: 99%
See 1 more Smart Citation